Behaviour of Titanium Dioxide Particles in Artificial Body Fluids and Human Blood Plasma - Korábková, Eva; Kašpárková, Věra; Jasenská, Daniela; Moricová, Dita; Daďová, Eliška; Truong, Thanh Huong; Capáková, Zdenka; Vícha, Jan; Pelková, Jana; Humpolíček, Petr (International journal of molecular sciences, 2021)
The growing application of materials containing TiO2 particles has led to an increased risk of human exposure, while a gap in knowledge about the possible adverse effects of TiO2 still exists. In this work, TiO2 particles of rutile, anatase, and their commercial mixture were exposed to various environments, including simulated gastric fluids and human blood plasma (both representing in vivo conditions), and media used in in vitro experiments. Simulated body fluids of different compositions, ionic strengths, and pH were used, and the impact of the absence or presence of chosen enzymes was investigated. The physicochemical properties and agglomeration of TiO2 in these media were determined. The time dependent agglomeration of TiO2 related to the type of TiO2, and mainly to the type and composition of the environment that was observed. The presence of enzymes either prevented or promoted TiO2 agglomeration. TiO2 was also observed to exhibit concentration-dependent cytotoxicity. This knowledge about TiO2 behavior in all the abovementioned environments is critical when TiO2 safety is considered, especially with respect to the significant impact of the presence of proteins and size-related cytotoxicity.
Keywords: Culture Media; osmolární koncentrace; Cell Line; Blood Donors; Saliva; Healthy Volunteers; krystalizace; koncentrace vodíkových iontů; voda; povrchové vlastnosti; Mice; Water; krevní plazma; Osmolar Concentration; sliny; Titanium; velikost částic; Surface Properties; Animals; zvířata; Crystallization; Humans; Hydrogen-Ion Concentration; plasma; viabilita buněk; kultivační média; Cell Survival; Fibroblasts; myši; TiO2 particles; agglomeration; simulated gastric fluids; buněčné linie; proteins; dárci krve; titan; Plasma; Metal Nanoparticles; kovové nanočástice; Particle Size; lidé; fibroblasty; zdraví dobrovolníci pro lékařské studie